Bond Market Development, Economic Growth, and the Role of Foreign Investment - Muharam, H; Ghozali, I; Denny Arfinto, E (KnE Social Sciences, 2018)
The aim of this research was to analyze the relationship among bond market development, economic growth, and foreign investment in several countries. The object of the research was sovereign bond with a sample of some developing countries in Asia, America, Europe, and Africa during the period of 2004–2015. The methods used were Vector Autoregressive (VAR), Vector Error Correction Model (VECM), and Granger causality. The result showed that there are short- and long-run cointegrations in each sample. On the other hand, there is no causality in all sample countries but there is only univariate correlation in Indonesia, Thailand, and Mexico. Keywords: sovereign bond, bond market development, economic growth, and foreign investment